Enhancing Digital Skill Understanding to Support Product and Marketing Innovation for Embroidery and Snack MSMEs within the Pajarakan Maju Small and Medium Industry (IKM) Cluster, Probolinggo Regency - Ummi Latifah; Adi Putra Darmawan; Sri Nurhasana; Beny Yusman; Saiful Rizal; Isyvina Unaizah Royya (Edusight Jurnal Pengabdian Masyarakat, 2026)
MSMEs play a crucial role in supporting both regional and national economic growth. However, the advancement of digital technology requires MSME operators to possess an adequate understanding of how technology can be leveraged for business development. A persistent challenge for MSMEs is a limited understanding of the digital skills that can be utilized to foster product innovation and enhance marketing efforts. This situation was observed among MSMEs belonging to the IKM Pajarakan Maju group in Probolinggo Regency—specifically Lili Bordir, Cindy Bordir, and Holifah Keripik. This community service initiative aimed to enhance MSME operators' understanding of the importance of digital skills in supporting product innovation and business marketing. The activity was conducted through a collaboration between Universitas Hafshawaty Zainul Hasan (UNHASA) and Universitas Pembangunan Nasional “Veteran” Jawa Timur (UPNVJT), employing a participatory approach that included observations, field visits, sharing sessions, interactive discussions, and evaluations. The results indicate that MSME operators gained valuable insights into using digital media for promotion, the importance of establishing a business identity on digital platforms, and opportunities for product innovation enabled by digital technology. Furthermore, the activity raised participants' awareness regarding the necessity of adapting to technological advancements to boost business competitiveness. Thus, this community service initiative has made a positive contribution to improving MSME operators' digital skills, serving as a foundational step toward developing businesses that are more adaptable to the evolving digital economy.